Auricular Reconstruction - Kurian, Keerthi E.; Oyer, Samuel L.; Park, Stephen S. (Facial Plastic Surgery, 2024)
The auricle is susceptible to various injuries due to its location and projection from the scalp. The unique contours of the external ear makes reconstruction a challenging endeavor. This chapter provides a comprehensive overview of auricular reconstruction, based on the depth, location, and size of injury. Strategies for reconstructing superficial, composite, and full-thickness injuries are discussed in relation to the location of the defect. Targeted reconstructive options for injuries of the upper, middle, and lower thirds of the auricle are outlined. Methods for total auricular reconstruction and auricular prosthesis are discussed. Options for managing traumatic injuries are reviewed, including avulsion/amputation injuries, burns, electrical injuries, frostbite, and human/animal bites. This chapter provides a practical framework for surgeons faced with complex auricular defects, offering insights to recreate a discreet, harmonious ear.
Keywords: ear; auricular reconstruction; ear reconstruction